A multimodal study of impulsivity and body weight: Integrating behavioral, cognitive, and neuroimaging approaches. Issue 1 (29th November 2016) - Filbey, Francesca M.; Yezhuvath, Uma S.
Abstract : Objective: Dimensions of impulsivity are related to obesity. Accordingly, characterization of impulsivity in individuals with overweight and obesity holds promise for more targeted and effective intervention. Methods: Forty‐five individuals (13 males, mean age = 32.6, mean body mass index [BMI] = 30.7) were recruited to determine the role of impulsivity in elevated body weight by evaluating: (1) trait impulsivity via impulsive sensation‐seeking scale (ImpSS), (2) state impulsivity via continuous performance test, and (3) activation and integration of brain cognitive control regions via functional magnetic resonance imaging during a response inhibition task (i.e., stop signal task). Results: Positive correlations were found between BMI and trait (ImpSS) as well as state impulsivity (continuous performance test, β ). BMI was negatively correlated with regional activation in the temporal lobe and insula during successful response inhibition. Further, there was a positive association between BMI and functional connectivity between the right inferior frontal gyrus and right middle frontal gyrus during successful response inhibition. Mediation analyses revealed that ImpSS mediated the relationship between BMI and neural response in the right inferior frontal gyrus. Conclusions: This multimodal study provides concordant evidence for behavioral, cognitive, and neural markers of impulsivity and elevated BMI, highlighting the need to address inhibitory control mechanisms for more effective weight management programs.